Extended dividend, cash flow and residual income valuation models: Accounting for deviations from ideal conditions - Nicolas Heinrichs; Dieter Hess; Carsten Homburg; Michael Lorenz; Soenke Sievers (University of Cologne, Centre for Financial Research (CFR), 2011)
Standard equity valuation approaches (i.e., DDM, RIM, and DCF model) are derived under the assumption of ideal conditions, such as infinite payoffs and clean surplus accounting. Because these conditions are hardly ever met, we extend the standard approaches, based on the fundamental principle of financial statement articulation. The extended models are then tested empirically by employing two sets of forecasts: (1) analyst forecasts provided by Value Line and (2) forecasts generated by cross-sectional regression models. The main result is that our extended models yield considerably smaller valuation errors. Moreover, by construction, identical value estimates are obtained across the extended models. By reestablishing empirical equivalence under non-ideal conditions, our approach provides a benchmark that enables us to quantify the errors resulting from individual deviations from ideal conditions, and thus, to analyze the robustness of the standard approaches. Finally, by providing a level playing field for the different valuation approaches, our findings have implications for other empirical settings, for example, estimating the implied cost of capital.
Keywords: G12; G14; M41; 330; Dirty Surplus; Terminal Value; Steady-State; Valuation Error